The economic burden of anxiety and depression in Indonesia: evidence from a cross-sectional web panel survey - Arulsamy, Karen; Effendy, Elmeida; Mardhiyah, Sarah; Amin, Mustafa M.; Husada, M. Surya; Camellia, Vita; Stona, Anne-Claire; Finkelstein, Eric Andrew (Frontiers in Public Health, 2025)
BackgroundMental health conditions are the second leading cause of disability in Indonesia, accounting for 13 percent of total years lived with disability. However, little is known about their broader economic impact. This study estimates the economic burden of anxiety and depression in adults, including healthcare costs and productivity losses, using a low-cost web panel approach that can be replicated in countries lacking data.MethodsA cross-sectional online survey was conducted with 5,828 Indonesian adults via a web panel. Participants completed the Patient Health Questionnaire-4 (PHQ-4) for themselves and household members, providing data on 16,096 individuals. Participants who screened positive for anxiety and/or depression symptoms based on the PHQ-4 (N = 438) were then asked about their healthcare utilization, days missed from work, and reduced productivity due to these symptoms. These responses were monetized and extrapolated based on the prevalence rate and population counts to generate per person and total annual costs.ResultsOverall, 14.7 percent reported symptoms consistent with anxiety or depression, yet over 60 percent were never formally diagnosed, highlighting a large diagnosis gap. Direct healthcare costs averaged IDR 2,111,020 per person annually. Employees reported 34 missed workdays per year and were 51 percent less productive while working. Indirect costs via absenteeism and presenteeism averaged IDR 5,178,312 and IDR 11,021,700 per person. The total annual economic burden was IDR 463,811.33 billion (USD 29.22 billion), or 2.1 percent of Indonesia’s GDP, with labor market productivity losses accounting for 88.5 percent of the total.ConclusionAnxiety and depression impose substantial health and economic costs in Indonesia. Low-cost, evidence-based interventions—particularly workplace-focused programs—could generate significant health and economic benefits.